Institutional Capacity and Public Vocational Training Service Quality in Responding to Digital Labor Market Challenges - Wahyuddin, Wahyuddin; Fadli, Zul (PUBLICUS: Jurnal Administrasi Publik, 2026)
The rapid digitalization of labor markets presents significant challenges for public vocational training institutions, requiring improvements not only in technical training but also in institutional capacity and service quality. This study examines the relationship between institutional capacity and the quality of public vocational training services in responding to the demands of the digital labor market. The research focuses on the UPT Balai Latihan Kerja (BLK) under the Department of Manpower and Transmigration of South Sulawesi Province, Indonesia, as a representative subnational public organization responsible for workforce development. A quantitative research design was employed using survey data collected from 210 respondents, including training participants, instructors, and administrative staff. Institutional capacity was measured through dimensions such as human resource competence, organizational structure and systems, leadership support, resource availability, and adaptive capacity to digital change. Service quality was assessed based on reliability, responsiveness, accessibility, transparency, and labor market relevance. Data were analyzed using descriptive statistics and multiple regression analysis. The findings reveal that institutional capacity has a significant and positive effect on service quality. Leadership support, human resource competence, and adaptive capacity emerged as the strongest predictors. These results indicate that governance capability plays a more decisive role than resource availability alone in shaping service performance. The study contributes to public administration literature by providing empirical evidence on how institutional factors influence service quality in public vocational training institutions within a digital transformation context. Practically, the findings emphasize the importance of capacity-oriented reforms to maintain institutional responsiveness, credibility, and labor market alignment.